Rushing for subsidies: The impact of feed-in tariffs on solar photovoltaic capacity development in China. (1st January 2021) - Dong, Changgui; Zhou, Runmin; Li, Jiaying
Highlights: The effect of China's feed-in tariff (FIT) on installed PV capacity is estimated. China's zonal FIT offers a quasi-natural experiment to analyze its policy effect. Subsidies have a much higher effect on installed PV capacity than was believed. Without the FIT policy, China's PV deployment could virtually disappear. The abatement cost of China's FIT is higher than the carbon-trading market. Abstract: Governments across countries often offer dynamic subsidies to clean technologies that decrease over time. However, the impact of government subsidies on technology deployment is difficult to gauge due to many confounding factors and the selection bias problem caused by the phenomenon of rushing for subsidies. This study takes China's solar photovoltaic (PV) as an example, and uses a difference-in-difference framework that leverages China's zonal feed-in tariff (FIT) policy design and its multiple changes over time. The parallel rushing for subsidies by two neighboring FIT zones provides a unique opportunity to identify the causal effect of FIT policy on newly installed PV capacity. Results show that an increase of 0.1 yuan/kWh (~$0.014/kWh) in PV subsidies adds about 18 GW/year of installed capacity to the national PV market, right in the middle of previous estimates in the literature. From a different perspective, if China did not have any PV subsidies, the PV deployment market would virtually disappear. The cost of carbon mitigation through PV feed-in tariffs is estimated at around 120 yuan (~$17) per ton of CO2 . Our estimate of the impact of FIT on PV capacity is useful for the government to design policies that help the PV industry transit to a subsidy-free era.